Does It Cost More to Train Residents or to Replace Them? - Wynn, Barbara O.; Smalley, Robert; Cordasco, Kristina M. (RAND Corporation, 2023)
The policy issue underlying this study is whether Medicare support for graduate medical education should be restructured to differentiate between self-sustaining or less costly programs and those that are more costly to the sponsoring institution and its educational partners. The authors used literature, interviews, and administrative data to explore how the financial impact of operating residency training programs might differ by specialty.